Analisis Kebijakan Harga Gula: Policy Analysis of Sugar Pricing - Sularso, R. Andi (Fenomena, 2004)
The Indonesian sugar industry faces persistent challenges in balancing domestic production, farmer welfare, and import dependence. This study examines how government-set sugar proveneu prices influence smallholder sugarcane farmers in Jember Regency, framed by agricultural price policy theory. The research aims to determine whether these price policies affect farmers’ planted area, productivity, and income. Using secondary time-series data from 1988 to 2002 obtained from BULOG and Semboro Sugar Factory, the study employs multiple linear regression analysis. The findings reveal that the sugar proveneu price does not significantly affect planted area or productivity, but it has a significant positive effect on farmers’ income. Additionally, the price of dry milled rice has a significant negative impact on sugarcane area, indicating that rising rice prices lead farmers to reduce sugarcane cultivation. The study concludes that while sugar price policy improves farmers’ income, it fails to stimulate area expansion or productivity gains. Recommendations include increasing sugar prices to boost production, utilizing by-products like molasses for additional revenue, and improving sugar quality for industrial markets. Future research should incorporate competing commodities such as fruits and vegetables. Industri gula Indonesia menghadapi tantangan berkelanjutan dalam menyeimbangkan produksi domestik, kesejahteraan petani, dan ketergantungan impor. Penelitian ini mengkaji pengaruh harga proveneu gula yang ditetapkan pemerintah terhadap petani tebu rakyat di Kabupaten Jember, dengan kerangka teori kebijakan harga pertanian. Penelitian bertujuan mengetahui apakah kebijakan harga tersebut mempengaruhi areal tanam, produktivitas, dan pendapatan petani. Menggunakan data sekunder deret waktu 1988–2002 dari BULOG dan Pabrik Gula Semboro, metode analisis regresi linier berganda diterapkan. Hasil penelitian menunjukkan bahwa harga proveneu gula tidak berpengaruh signifikan terhadap areal maupun produktivitas, tetapi berpengaruh positif signifikan terhadap pendapatan petani. Selain itu, harga gabah kering giling berpengaruh negatif signifikan terhadap areal tebu, artinya kenaikan harga gabah mendorong petani mengurangi areal tebu. Kesimpulannya, kebijakan harga gula meningkatkan pendapatan namun gagal mendorong perluasan areal atau peningkatan produktivitas. Rekomendasinya meliputi peningkatan harga gula, pemanfaatan limbah industri seperti tetes, serta peningkatan kualitas gula untuk pasar industri. Penelitian lanjutan perlu menyertakan komoditas pesaing seperti buah dan sayur.